Evidence of Significant Central Fatigue in Patients with Cancer-Related Fatigue during Repetitive Elbow Flexions till Perceived Exhaustion - WALSH, THOMAS (My University, 2014)
OBJECTIVE: To investigate whether fatigue induced by an intermittent motor task in patients with cancer-related fatigue (CRF) is more central or peripheral. METHODS: Ten patients with CRF who were off chemo and radiation therapies and 14 age-matched healthy controls were enrolled. Participants completed a Brief Fatigue Inventory (BFI) and performed a fatigue task consisting of intermittent elbow-flexion contractions at submaximal (40% maximal voluntary contraction) intensity till self-perceived exhaustion. Twitch force was elicited by an electrical stimulation applied to the biceps brachii muscle. The relative degree of peripheral (muscle) vs. central contribution to fatigue induced by the intermittent motor task (IMT) was assessed using twitch force ratio (TF ratio) defined as post IMT twitch force to pre IMT twitch force. The total number of trials (intermittent contractions) and total duration of all trials performed by each subject were also quantified. RESULTS: BFI scores were higher (p < 0.001) in CRF than controls, indicating greater feeling of fatigue in CRF patients than controls. A significantly smaller number of trials and shorter total duration of the trials (p < 0.05) were observed in CRF than control participants. The TF ratio (0.81 ± 0.05) in CRF was higher (p < 0.05) compared with that of controls (0.62 ± 0.05), suggesting CRF patients experienced a significantly lower degree of muscle (peripheral) fatigue at the time of perceived exhaustion. CONCLUSION: Consistent with prior findings for fatigue under submaximal sustained contraction, our results indicate that motor fatigue in CRF is more of central than peripheral origin during IMT. Significant central fatigue in CRF patients limits their ability to prolong motor performance.
Keywords: Cancer; Cancer; SYMPTOMS